One of these things is sort of like the other: presidential approval and support for government management of the economy in Chile, 2006-2013 - Perelló, Lucas (Política. Revista de Ciencia Política, 2015)
The economic vote is one of the most accepted theories of political science. Studies on the subject have mainly focused on developed democracies, leaving aside the effects that economic performance holds in different settings. Thispaper provides further answers by examining the case of Chile. Since 2006, Chileans have experienced different economic settings, which include a recession and a period of ensuing growth. However, economic performance did not translate into support or disapproval for sitting presidents. On thecontrary, Bachelet’s popularity skyrocketed in the midst of an economic crisis, while Piñera’s approval drastically fell when the economy was doing well. A similar outcome occurred for views on the government’s economic management. Hence, this paper puts forward the hypothesis that—controlling by socio demographic, political and economic variables—Chileans were limited in discerning between presidential approval and the responsibility for economic management between 2006 and 2013. To test this assumption, I use survey data from the Centro de Estudios Públicos (CEP) and run logistic regression models and predictive margins. Results show that sex, age, region ofresidence and economic outlook explain both types of assessments in a similar manner. There are, however, important differences within and between models, particularly for the variables socioeconomic status and political ideology.